Enhanced Electrochemical H2 Evolution by Few‐Layered Metallic WS2(1−x)Se2x Nanoribbons. (9th September 2015) - Wang, Fengmei; Li, Jinshan; Wang, Feng; Shifa, Tofik Ahmed; Cheng, Zhongzhou; Wang, Zhenxing; Xu, Kai; Zhan, Xueying; Wang, Qisheng; Huang, Yun; Jiang, Chao; He, Jun
Abstract : As an effective alternative to noble platinum electrocatalyst, earth abundant and inexpensive layered transition metal dichalcogenides (TMDs) are investigated for the hydrogen evolution reaction (HER). Compared with binary TMDs, the tunably composed ternary TMDs have hitherto received relatively little attention. Here, few‐layered ternary WS2(1− x ) Se2 x nanoribbons (NRs) with metallic 1T phases, much more catalytically active in HER, are prepared for the first time. The favorable Δ G H o introduced by the tensile region on the surface, along with the presence of local lattice distortions of the WS2(1− x ) Se2 x nanoribbons with metallic 1T phases, greatly promotes the HER process. These ternary NRs achieve the lowest overpotential of ≈0.17 V at 10 mA cm −2 and a Tafel slope of ≈68 mV dec −1 at a low catalyst loading (≈0.30 ± 0.02 mg cm −2 ). Notably, the long‐term durability suggests the potential of practical applications in acid electrolytes. The results here suggest that the ternary WS2(1− x ) Se2 x NRs with 1T phases are prominent alternatives to platinum‐based HER electrocatalysts. Abstract : Few‐layered ternary WS2(1– x ) Se2 x nanoribbons (NRs) with metallic 1T phases are prepared. The favorable Gibbs free energy for hydrogen absorption (Δ G H o ) of the WS2(1– x ) Se2 x NRs, introduced by the tensile region and local lattice distortions, greatly promotes the hydrogen evolution reaction (HER). The results suggest that the metallic WS2(1– x ) Se2 x NRs are potential alternatives for HER electrocatalysts.